Pengembangan Bahan Ajar Matematika Berbentuk Komik untuk Meningkatkan Kemampuan Matematis Siswa Kelas VII SMP - Tiara F ikriani; Mirda Swetherly Nurva (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2020)
This purpose of this research is developing mathematics teaching materials that present in comics for student in grade seventh of junior high school. Using teaching materials in the learning process is one way to help the students to be understand about learning materials. The teaching materials that provided for students must have three criterias are valid, practical, and effective. The type of this research is the Research and Development (R and D) and using the Plomp development model. This research consist of investigation phase, development or prototype phase, and assessment phase. The results of this development research are: (1) The validity of the teaching materials are valid with a percentage 90% on the material aspect and the material Design (2) practicality of teaching materials based on the response of teachers and students are Practice with percentage 83.5% (3) The effectivity of teaching materials are effective based on communication skills of students with a percentage of 73%.